TM9SF4 is a potential prognostic biomarker in hepatocellular carcinoma - Yahui Ma; Lingling Guo; Bo Zhang; Ting Wang; Qingchun Feng (Discover Oncology)
Abstract Background The transmembrane 9 superfamily protein member 4 (TM9SF4) is a transmembrane protein upregulated in multiple cancers; however, its role in hepatocellular carcinoma (HCC) remains unknown. Methods The Cancer Genome Atlas (TCGA), Genotype-Tissue Expression (GTEx) and International Cancer Genome Consortium (ICGC) databases were utilized to investigate the differential expression of TM9SF4 in HCC and tumor tissues. The prognostic and value of TM9SF4 in HCC was evaluated using Kaplan–Meier analysis, Cox regression, and receiver operating characteristic (ROC) curve analyses. The expression pattern and prognostic value of TM9SF4 was further verified using immunohistochemical (IHC) examination of 87 pairs of HCC clinical specimens. A nomogram was constructed by combining TM9SF4 expression and clinicopathological parameters to predict prognosis for individual patient. Additionally, gene set enrichment analysis (GSEA) was performed to identify key pathways related to TM9SF4. Results TM9SF4 expression was upregulated in the HCC tissues. High expression of TM9SF4 was significantly associated with advanced T stage, histological grade, and worse survival. Multivariable Cox analysis revealed that TM9SF4 expression was an independent factor for overall survival. The nomogram by incorporating the TM9SF4 and T stage showed good performance in predicting prognosis. Moreover, GSEA analysis revealed that TM9SF4 was functionally involved in pathways associated with the cell cycle. Conclusions These findings suggest that TM9SF4 is a promising biomarker with prognostic potential and functional significance in HCC.